Audit Quality Determinant at a Public Accounting Firm in Surabaya - Ruci Arizanda Rahayu; Wiwit Hariyanto; Eny Maryanti (Politeknik Negeri Madiun, 2023)
This study aims to examine the determinants of audit quality at a public accounting firm in Surabaya. The primary data collection method used in this research is a questionnaire method which is distributed to the Auditors of Public Accounting Firms in the Surabaya area. The data collected were 129 respondents. This research uses multiple linear analysis method with SPSS 26 data processing tool. The results of this study indicate that independence has a significant effect on audit quality. Audit experience has a significant effect on audit quality. Audit Tenure has a significant effect on audit quality.